KONDISI EMOSI KELUARGA PASIEN RAWAT INAP PENYAKIT DALAM DI RUMAH SAKIT UMUM DAERAH (RSUD) PARIAMAN TAHUN 2014 - Loli, Fitri - (Bimbingan dan Konseling, 2014)
This research is motivated because of the families of patients who have unstable emotions. Angry with the patients family health services provided by medical personnel, the patients family to see the state of excessive sadness the family or the patient being treated, the fear experienced by the patient because of the patients family has long cared for but does not go well, too concerned with the patients family health state of the patient. The purpose of this study describe: 1) The condition of negative emotions family medicine inpatients. 2) The condition of a family of positive emotions in internal medicine inpatients. This type of research is descriptive quantitative research. The population numbered 28 people. Sampling using total sampling the number 28. The technique used to analyze the data is the percentage techniques. These results indicate that the negative emotional state family medicine inpatients in the category quite emotional with the percentage 60.71%. While a positive emotional state inpatient family medicine is in the category of emotion with the percentage of 75.00%. Based on the findings of this study recommended to the hospital in order to improve medical services and hospitals to the counselor to be able to create a program of services that can help families cope emotionally unstable patients.